Pengolahan Air Gambut Untuk Menurunkan Kadar Besi Dan Mangan Dengan Proses Elektrokoagulasi Secara Kontiniu - Adam Fadillah; Idral Amri; Syaiful Bahri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Peat water from surface water or groundwater has high organic content and there is a metal content inside such as ferrous metals and Mn. Therefore it is necessary to do the processing by using electrocoagulation. The purpose of this study is to discuss the performance test of the electrocoagulation process continuously on the decrease of Fe and Mn levels and determine the optimum condition. The electrocoagulation process uses electric power that flows in the direction of the electrode. Electrocoagulation reactors paired with cables that connected the power supply to an electric current with varying voltages (18, 20, 22, and 24 volts) and variations in flow rate (4 and 6 lpm) are employed. The results of this study obtained the optimum conditions obtained at 24 volt voltage and 4 lpm flow rate with decrease of Fe by 89% from 2,909 mg/L to 0,322 mg/L and Mn equal to 92% from 0,232 m /L to 0,019 mg/L. Keywords: peat water, electrocoagulation, flow rate, continuous, voltage